Misoprostol vaginal insert versus misoprostol vaginal tablets for the induction of labour: a cohort study - Daniele Bolla; Saskia Vanessa Weissleder; Anda-Petronela Radan; Maria Luisa Gasparri; Luigi Raio; Martin Müller; Daniel Surbek (BMC, 2018)
Abstract Background Misoprostol vaginal insert for induction of labor has been recently reported to be superior to dinoprostone vaginal insert in a phase III trial, but has never been compared to vaginal misoprostol in another galenic form. The aim of this study was to compare misoprostol vaginal insert (MVI) with misoprostol vaginal tablets (MVT) for induction of labor in term pregnancies. Methods In this retrospective cohort study we compared 200 consecutive women induced with 200-μg misoprostol 24-h vaginal insert (Misodel®) with a historical control of 200 women induced with Misoprostol 25-μg vaginal tablets (Cytotec®) every 4-6 h. Main outcomes variables included induction-to-delivery interval, vaginal delivery within 24-h, incidence of tachysystole, mode of delivery, and neonatal outcome. A subanalysis in the MVI group was performed in order to identify predictive factors for tachysistole and vaginal delivery within 24 h. Results The time from induction to vaginal delivery was 1048 ± 814 min in the MVI group and 1510 ± 1043 min in the MVT group (p < 0.001). Vaginal delivery within 24-h occurred in 127 (63.5%) patients of the MVI group and in 110 (55%) patients of the MVT group (p < 0.001). Tachysystole was more common in the MVI group (36% vs. 18%; p < 0.001). However, no significant predictors of uterine tachysystole in MVI group have been identified in crude and fully adjusted logistic regression models. Bishop score was the only predictor for vaginal delivery within 24 h (p < 0.001) in MVI group. Caesarean delivery rate (27% vs. 20%) and vaginal-operative deliveries (15.5% vs. 15.5%) did not differ significantly between the two groups. Neonatal outcomes were similar in both groups. Conclusions MVI achieves a more vaginal delivery rate within 24 h and Tachysystole events compared to MVT. However, no differences in caesarean section, operative vaginal delivery, and neonatal outcomes are reported. No predictors of tachysistole after MVI administration have been identified. Bishop score and parity are the only predictors of vaginal delivery within 24 h after MVI administration.